Forced absenteeism: employee rights and employer responsibility - Tkachenko, Olha (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The purpose of the article is a systematic analysis of the legal nature of the concept of «forced absenteeism», the application of this legal construction in labor legislation, an outline of cases in which this phenomenon occurs, and a study of the consequences of forced absenteeism for parties to labor relations.The Constitution of Ukraine grants every person, regardless of citizenship, gender, nationality, and other defining characteristics, the right to work and provide oneself with the basic means of subsistence. This constitutional right can be exercised at one's own will. However, unfortunately, there are many cases when a person is deprived of the opportunity to work (perform the labor function directly) and, thereby, receive wages as a means of subsistence.The national legislation uses the legal construction «enforced absenteeism» to define the specified legal situation. However, none of the acts of the current legislation discloses the definition of this concept, despite its repeated use, in particular in the Code of Labor Laws. Disclosure of the essence of this concept (legal situation) is possible only through the interpretation of the provisions of Article 235 of the Code of Labor Laws, other normative acts and court decisions.The article examines the legal nature of forced absenteeism as a case that makes it impossible for an employee to perform his work functions and, at the same time, is a violation of the constitutional right of every person to work and receive income. Jurisprudence on the consideration of labor law cases regarding forced absenteeism was analyzed and general conclusions were made regarding the interpretation of this legal phenomenon and the clarification of cases in which it may occur.The article also examines the possible legal consequences for the employee in the case of forced absenteeism, which consist in applying to the court with legal claims for recovery from the employer (the defendant in the case) in favor of the employee of the average salary during the forced absenteeism, reinstatement and protection of the right to annual vacation